Evaluation of medicine use behaviors of adult patients in a rural area: A cross-sectional study from Turkey - Hakan Alan; Mahcube Cubukcu; Eda C. Guzel; Latife M. Yildiz (Journal of Family Medicine and Primary Care)
Background/Purpose: This study aimed to determine the medicine usage behaviors of patients (>65 years) registered to the family health care center (FHCC) in a rural area. Methods: This cross-sectional and descriptive study was performed on 224 geriatric patients admitted to the FHCC in Terme town of Samsun between January 2018 and March 2018. The questionnaire consisting of 29 questions about sociodemographic characteristics, knowledge of drugs, and usage habits was applied to the participants by using the face-to-face interview technique. SPSS (version 23.0. SPSS Inc. Chicago. IL. USA) program was used in the analysis. P values of less than 0.05 were considered significant. Results: The mean age was 73.01± 0.3.14 years, 53.19% were male, 87.4% were married, and 52.9% had chronic diseases. Of all participants, 56% stated that they visited physicians when they got ill; 22% used drugs at home without consulting a physician. The presence of chronic disease appears to be associated with keeping drugs at home (P = 0.023). The most common medicines consumed without a prescription were painkillers; 67.6%. 20.9% of the participants stated recommending medication to their surroundings related to their level of education (P = 0.011). Furthermore, 24.9% stated that they had stopped their medications before the recommended time. Moreover, 82.9% of the group read the instructions before use. Those signs were more significant in males and in those >75 years old (P = 0.001 and P = 0.024, respectively). Conclusion: Rational use of medicine was associated with gender, chronic disease, and educational level in geriatric patients. The importance of rational drug use in society should be explained by individual characteristics.